Health education provided by nurses to children and young people: parents’ assessment - Anabela Fonseca Pereira; Joaquim José Jacinto Escola; Carlos Manuel Torres Almeida; Vítor Manuel Costa Pereira Rodrigues (BMC Nursing, 2023)
Abstract Background Healthy literacy is a determinant key children/teenager’s health and health outcomes. The aim of this study to identify the parents’ assessment about Health Education practice to children and teenagers. Methods We opted for a descriptive, quantitative and cross-sectional research, with a non-probabilistic convenience sample. The inclusion criteria were: being a parent who uses attending children health appointments in primary health care; being a parent who has a child hospitalized and is accompanying him/her in the pediatric hospital inpatient ward. A questionnaire survey was built with three sections: sample characterization, Health Education practices performed by nurses (5 questions) and a scale that measured Health Education Assessment Scale (HEAS), which contained 48 items and was validated. It was applied from September to December 2018. Results The survey was filled in by 113 parents. The results showed that 100% (n = 113) of the parents feel comfortable to talk with nurses about children/teenagers health; 79.6% (n = 90) consider that nurses have time availability for the doubts clarification; 61.9% (n = 70) point out that nurses identify child/teenager needs; Healthy eating” (60.2%; n = 68), the “National Vaccination Plan” (53.1%; n = 60) and “Harmful behaviors prevention” (46.9%; n = 53) are the most important topics; 56.6% (n = 64) of the parents, when in doubt, turn first to the pediatrician, and 66.4% (n = 75) considered that this practice was equal important, compared with other nursing interventions. Discussion This study shows that Health Education provided by nurses is based on the need’s identification, with a perspective of involvement and participation, promoting health and conscious changes which reinforces the nurses’ position as health educators.